POTENTIAL OF USING NEEM SEED KERNEL POWDER FOR THE CONTROL OF PULSE BEETLE CALLOSOBRUCHUS CHINENSIS INFESTING KHESARI SEEDS INSTORAGE - SINGH, S. C.; KUMARISINGH, BINDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Investigation was carried out on the effect of the Neem Seed Kernel (NSK) powder as seed protectant against Callos obruchus chinensis (Coleoptera : Bruchuidae). The test compound of different dosages was effecting in reducing the percentage of grain damage as compared to control. These seeds suggested that NSK powder to be pest effective, safer to predators, economically viable and socially acceptable by the farmers of the region.